2001
DOI: 10.1016/s0960-9822(01)00070-7
|View full text |Cite
|
Sign up to set email alerts
|

Dosage compensation in birds

Abstract: The Z and W sex chromosomes of birds have evolved independently from the mammalian X and Y chromosomes [1]. Unlike mammals, female birds are heterogametic (ZW), while males are homogametic (ZZ). Therefore male birds, like female mammals, carry a double dose of sex-linked genes relative to the other sex. Other animals with nonhomologous sex chromosomes possess "dosage compensation" systems to equalize the expression of sex-linked genes. Dosage compensation occurs in animals as diverse as mammals, insects, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 22 publications
6
79
0
Order By: Relevance
“…It seems clear that Z chromosome inactivation does not occur (Schmid et al 1989). There are reports of equalized expression levels in males and females for a limited number of Z-linked genes (Kuroda et al 2001;McQueen et al 2001), possibly regulated at the level of transcription since both Z chromosomes of male chicken are transcribed (Kuroda et al 2001;Kuroiwa et al 2002). The observations of a heterogeneous, noncoding RNA that accumulates on the Z chromosome in the female nucleus but is heavily Figure 3.…”
Section: Discussionmentioning
confidence: 98%
“…It seems clear that Z chromosome inactivation does not occur (Schmid et al 1989). There are reports of equalized expression levels in males and females for a limited number of Z-linked genes (Kuroda et al 2001;McQueen et al 2001), possibly regulated at the level of transcription since both Z chromosomes of male chicken are transcribed (Kuroda et al 2001;Kuroiwa et al 2002). The observations of a heterogeneous, noncoding RNA that accumulates on the Z chromosome in the female nucleus but is heavily Figure 3.…”
Section: Discussionmentioning
confidence: 98%
“…Recent quantitative RT-PCR data, however, show expression equalisation of several Z-linked genes in male and female chicken embryos. (65) Meanwhile, a separate study using fluorescent in situ hybridisation to nascent mRNAs has shown that these Z-linked genes are transcribed from both Z chromosomes in male cells. (66) Therefore, if dosage compensation does occur, it does not involve widespread inactivation of one sex chromosome, as occurs in mammals.…”
Section: Dmrt1 and The Z Dosage Hypothesismentioning
confidence: 99%
“…Hypothetically, it is governed either by a dominant gene linked to the Wchromosome or by the amount of Z-chromosome dosage (Ellegren, 2000). On the basis of the studies that suggest the existence of compensation system for Z-chromosome linked genes (McQueen et al, 2001), the latter mechanism is less probable than the former.…”
Section: Introductionmentioning
confidence: 99%